Advances in the pharmacological effects and molecular mechanisms of emodin in the treatment of metabolic diseases - Yu, Linyuan; Zhao, Yongliang; Zhao, Yongli (Frontiers in Pharmacology, 2023)
are traditional Chinese medicines that have been used for thousands of years. They are formulated into various preparations and are widely used. Emodin is a traditional Chinese medicine monomer and the main active ingredient in Rhubarb palmatum L., Polygonum multijiorum Thunb. and Polygonum cuspidatum Sieb. Et Zucc. Modern research shows that it has a variety of pharmacological effects, including promoting lipid and glucose metabolism, osteogenesis, anti-inflammatory and anti-autophagy effects. Research on the toxicity and pharmacokinetics of emodin can promote its clinical application. This article aims to provide a basis for further development and clinical research of emodin in the treatment of metabolic diseases. Comprehensive summary of the pharmacology and molecular mechanisms of emodin in treating metabolic diseases by searching databases such as Web of Science, PubMed, ScienceDirect, and CNKI up to 2023. In addition, this article also analyzes the toxicity and pharmacokinetics of emodin. The results show that emodin mainly regulates AMPK, PPAR and inflammation-related signaling pathways, and has a good therapeutic effect on obesity, hyperlipidemia, non-alcoholic fatty liver disease, diabetes and its complications, osteoporosis, etc., while controlling toxic factors and improving bioavailability are of great significance for its clinical application.